INOVASI PELAYANAN KESEHATAN PUBLIC SAFETY CENTER 119 (PSC 119) SMASH CARE’S DI KOTA SOLOK - Wike Yuliana; Roni Ekha Putera; Yoserizal Yoserizal (Universitas Muhammadiyah Mataram, 2020)
Health service inovation Public safety Center 119 (PSC 119) Solok Madinah Sehat Cara Revolusi Sehat (SMASH CARE’S) in Solok City. For increasing the service in health sector, the govermnent of Solok City launched an inovation in health service PSC 119 Smash Care’s. this research intended to find out the implementation of Smash Care’s and also the public services that accepted by solok society. This research is using descriptive approach by qualitative methods. Technique of collecting the data was by interview and documentation. The result of this research shows that PSC 119 Smash Care’s give the emergency services to Solok society or the people who are in the Solok City. This service is very assist for the society. In the other hand, this service has more advantage than other. Those are easy to acces the service by direct call to 119 and also giving 24 hours service, free of charger and in accordance with needs and taking into account community complaints. But there are still some shortcomings such as the fraudulent numbers to call center 119, the lack of facilities and infrastructure as well and the lack of maximum socialization